Tea Polyphenols Improve Down-Regulation of Mitochondrial Functional Gene Expression Induced by Bisphenol A in Zebrafish Ovaries - Dai, Xiaoxin; Qiu, Lijun; Zhang, Han; Xu, Chunying; Zhao, Bo; Gao, Yang; Li, Haidong; Mu, Yi; Chu, Zhangjie (Frontiers in Marine Science, 2022)
The plasticizer bisphenol A, a typical endocrine disrupting chemical, is widely present in the environment. Previous studies demonstrated that exposure to bisphenol A can cause reproductive toxicity, abnormal fertilization and infertility. However, the mechanisms of low-concentration bisphenol A on the reproductive system and treatment measures have not been fully determined. In this study, we explored the transcriptomic profiles of female zebrafish ovaries. The transcriptomic data revealed that mitochondrial NADH dehydrogenase (mt-Nd) genes was significantly down in bisphenol A-exposed group, while co-administration of tea polyphenols remarkably elevated the expression of mt-Nd genes. To further explore the expression pattern of the mt-Nd, we analyzed the expression of six mt-Nd genes on different days by qRT-PCR in control, bisphenol A-exposed and bisphenol A-tea polyphenols ovaries. Here, we found that 0.1 mg/L bisphenol A exposure adversely affected mitochondrial respiratory chain in ovaries, may lead to reproductive disorders. Finally, our study demonstrated that tea polyphenols played a protective role in ovarian mitochondrial dysfunction in low-concentration bisphenol A-exposed female zebrafish.